2019
DOI: 10.1530/erc-19-0325
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of thyroid cancer driven by known and novel ALK fusions

Abstract: ALK fusions are found in various tumors, including thyroid cancer, and serve as a diagnostic marker and therapeutic target. Spectrum and outcomes of ALK fusions found in thyroid nodules and cancer are not fully characterized. We report a series of 44 ALK-translocated thyroid neoplasms, including 31 identified preoperatively in thyroid fine-needle aspirates (FNA). The average patients’ age was 43 years (range, 8–76 years); only one with radiation history. All 19 resected thyroid nodules with ALK fusion identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 43 publications
(58 reference statements)
0
38
0
1
Order By: Relevance
“…ALK rearrangement is common in PDTCs with a prevalence of 16%; striatin ( STRN )- ALK rearrangement is the commonest and rarely EMAP like 4 ( EML4 )- ALK [ 95 , 96 ]. Neurotrophic tyrosine kinase receptor ( NTRK ) fusion oncogenes ( NTRK3 / ETV6 , NTRK1 - TPR and NTRK1 - LMNA and NTRK1 - TMP3 ) are recognised in up to 26% of PTCs.…”
Section: Tumour Progressionmentioning
confidence: 99%
“…ALK rearrangement is common in PDTCs with a prevalence of 16%; striatin ( STRN )- ALK rearrangement is the commonest and rarely EMAP like 4 ( EML4 )- ALK [ 95 , 96 ]. Neurotrophic tyrosine kinase receptor ( NTRK ) fusion oncogenes ( NTRK3 / ETV6 , NTRK1 - TPR and NTRK1 - LMNA and NTRK1 - TMP3 ) are recognised in up to 26% of PTCs.…”
Section: Tumour Progressionmentioning
confidence: 99%
“…Only one other ITSN2 (exon 29)- ALK (exon 18) fusion has been reported so far, specifically in a patient with thyroid cancer. 33 In that case, RNA-Seq showed overexpression of ALK exons 18-29 downstream of the fusion point; however, neither IHC results nor the therapeutic effects of ALK-TKIs were reported.…”
Section: Discussionmentioning
confidence: 90%
“…All 5 PDTCs carried the STRN-ALK fusion. Compared to EML4-ALK, STRN-ALK may be more common in PDTC, and ∼10% of ALK fusions involve rare gene partners [ 17 ]. In the same study, Panebianco et al showed that all 19 resected thyroid nodules with ALK fusions identified preoperatively by fine-needle aspiration were malignant [ 17 ].…”
Section: Discussionmentioning
confidence: 99%